Sol‐gel–mediated synthesis of TiO2 nanocrystals: Structural, optical, and electrochemical properties. Issue 3 (20th December 2019) - Sharma, Reetu; Sarkar, Anjana; Jha, Ranjana; Kumar Sharma, Amit; Sharma, Darshan
Abstract: Nanoparticles of titanium dioxide were prepared using the sol‐gel method without any impurity. Rietveld refinement of XRD data confirmed the anatase phase of synthesized nanoparticles with space group I 41/ amd (141). XRD pattern revealed the crystalline nature of synthesized nanopowder. The average crystallite size of synthesized nanoparticles was calculated 7.5 nm. The electrochemical performance of synthesized TiO2 nanopowder was investigated as working electrode. The electrochemical reaction was found diffusion‐controlled as observed from cyclic voltammetry (CV) studies at different scan rates. The diffusion‐controlled charge storage mechanism also confirmed by charge transfer resistance and Warburg impedance, as calculated from the EIS analysis. SEM micrograph showed the plate‐like structure grown in cluster cloud of particles of synthesized TiO2 nanocrystals. Absorbance and optical bandgap were obtained using UV‐Vis spectra. De‐convoluted PL spectra provided the emission pattern from the ultra‐violet region to green region due to the presence of interstitial oxygen vacancies. The tune bandgap with EIS measurements of synthesized TiO2 nanoparticles offers its potential application in energy storage devices and photovoltaic applications. Abstract : TiO2 nanoparticles are synthesized by using simple and economic sol‐gel method. The techniques like XRD, SEM, UV‐VIS., PL, FT‐IR and electrochemical studies are used to structurally and optically characterize the synthesized nanoparticles